Synthesis of Co–Sn intermetallic nanocatalysts toward selective hydrogenation of citral. Issue 33 (3rd August 2016) - Zhou, Junyao; Yang, Yusen; Li, Changming; Zhang, Shitong; Chen, Yudi; Shi, Shuxian; Wei, Min
Abstract : Three Co–Sn intermetallic compound catalysts are prepared via a hydrotalcite approach, which show satisfactory catalytic performance toward selective hydrogenation of citral. Abstract : In this work, three supported Co–Sn intermetallic compound (IMC) catalysts (Co2.9 Sn2, CoSn and CoSn2 ) with a particle size of ∼20 nm were prepared via a facile hydrotalcite approach, and their catalytic performances were evaluated in the selective hydrogenation of citral to unsaturated alcohols (geraniol and nerol). EXAFS, in situ CO-FTIR and DFT calculation results reveal that the introduction of Sn in Co–Sn IMCs dramatically optimizes the geometric and electronic structures of active Co, in which Sn isolates the Co active-site and electron transfer occurs from Sn to the Co atom. H2 -TPD measurements indicate the presence of four different Co sites (labeled as α, β, γ and σ) on the surface of these IMCs; the sample of CoSn IMC shows the largest β/(γ + σ) ratio, which results in the highest selectivity toward unsaturated alcohols ( S UA : 67.6%). DFT studies prove that the geometric and electronic effects of the CoSn IMC weaken the hydrogenation of the CC group, accounting for the largely enhanced hydrogenation selectivity of citral to unsaturated alcohols.